Dual-Platform Automated Logistics Management System with Real-Time Tracking - TEOH WEI JUN; Sulaiman, Nur Liyana (Applied Information Technology And Computer Science, 2025)
The logistics industry depends on efficient deliveries, but Eco Haulage Sdn Bhd, a haulage company, still relies on manual processes, resulting in inefficiencies and errors. This project aims to tackle the problems by introducing a Dual-Platform Automated Logistics Management System with Real-Time Tracking. This project’s objectives are to design a system using object-oriented approach, to develop the system using web and Android technology, and to test the system using functionality testing and user acceptance testing (UAT). Software Development Life Cycle methodology is adopted, with Laravel for the web platform, Flutter for the Android mobile application, and Supabase as the database. Functionality testing recorded 100% pass rate, while UAT using System Usability Scale yielded an overall score of 85.36%, indicating usability. Future enhancements include expanding support to iOS and other platforms to improve accessibility. This project enhances logistics operational efficiency and provide a replicable blueprint for small and medium-sized logistics companies.